PENINGKATAN KEMAMPUAN MEMBACA CEPAT MELALUI METODE LATIHAN PADA SISWA KELAS VII B SMP NEGERI 15 MANOKWARI TAHUN AJARAN 2014/2015 - Syufi, Herman (Universitas Papua Manokwari, 2016)
Reading skills is not the word for word, but reading skills have a goal to get the meaning of the passage. Therefore, the reading speed is determined also by the ability to grasp the meaning of a word row.This study aimed at improving the language skills of students in secondary education with the title: “Improvement of Fast Reading Through Exercise Methods in Class VII B SMP Negeri 15 Manokwari”. Subjects in this study of teachers and students of class VII B SMP Negeri 15 Manokwari. The object of this research is the application of the method of speed readingexercises to improve reading skills. Actions are conducted in two cycles with steps such as planning, action, observation, observation and reflection, then the data collection is done by: (1) descriptive qualitative method of data collection in three ways, namely (a) read and write tests, (b) observation sheets, and (c) teacher observation sheet. The results showed that the classroom action research (PTK) conducted on students of Class VII B SMP Negeri 15 Manokwari, get a picture as follows. First, the use of speed reading training methods (sciming) can improve students’ reading ability. Secondly, referring to the results of observation and reflection can actually give a positive answer that the learning outcome by the number of 24 students (16 male students, female 8 students). Thirdly, it is known that increased activity of students inthe first cycle is only about 29% is represented by one person learners who scored 90 and 6 students who scored 80 there are 6 students. Fourth, cycle II can be seen that the acquisition value of the students is in line with expectations of researchers.